PROPOSTA DE UM FLUXO DE COORDENAÇÃO ESPACIAL 3D EM BIM: ESTUDO DE CASO EM UMA EDIFICAÇÃO RESIDENCIAL UNIFAMILIAR - Araujo, Andrew de; Melo, Reymard (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The BIM use for 3D coordination is one of the most beneficial and common uses of BIM, yet the professionals who carry out such an activity still do so in different ways through processes that are not yet as deeply described. In order to reach this goal, it is necessary to confront the existing literature with the processes carried out by professionals in the area, seeking barriers and innovations, what has been done this paper, in order to propose a workflow of 3D coordination that considers the segmented virtual construction, a practice that has proven to be common in projects that still have a low level of BIM maturity. The result of the research allows the continuation of the debate of the theme focusing on the priority between disciplines and the participation of members of the executive team in the coordination stage, which converges with BIM work methodology.